2011
DOI: 10.1093/rheumatology/ker281
|View full text |Cite
|
Sign up to set email alerts
|

Age at treatment predicts reason for discontinuation of TNF antagonists: data from the BIOBADASER 2.0 registry

Abstract: In conclusion, factors predicting discontinuation of TNF antagonists due to AEs are older age and diagnosis of RA. On the other hand, younger age predicts discontinuation due to lack of efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 17 publications
2
24
0
2
Order By: Relevance
“…AS patients treated with a first TNF inhibitor had a good overall drug survival rate, with 79% of patients remaining on treatment after 2 yr. By contrast, RA patients treated with a first TNF inhibitor had a continuation rate of 44% after 1 yr. These findings are consistent with those of previous studies, including the Danish DANBIO (13, 14), Spanish BIOBADASER (16, 21), and a Norwegian study (22). Although other factors might influence the retention rates of TNF inhibitors, drug survival can be regarded as a surrogate marker for efficacy.…”
Section: Discussionsupporting
confidence: 93%
“…AS patients treated with a first TNF inhibitor had a good overall drug survival rate, with 79% of patients remaining on treatment after 2 yr. By contrast, RA patients treated with a first TNF inhibitor had a continuation rate of 44% after 1 yr. These findings are consistent with those of previous studies, including the Danish DANBIO (13, 14), Spanish BIOBADASER (16, 21), and a Norwegian study (22). Although other factors might influence the retention rates of TNF inhibitors, drug survival can be regarded as a surrogate marker for efficacy.…”
Section: Discussionsupporting
confidence: 93%
“…More deaths were observed in ADA+MTX patients versus PBO+MTX patients, which is inconsistent with previous clinical trial experience 18. Advanced age and comorbidities have been reported in some analyses as risk factors for immunomodulatory therapy toxicity 1922. Older patients were over-represented, with four of six deaths in the ADA+MTX arm occurring in patients over 70 years old.…”
Section: Discussionmentioning
confidence: 70%
“…On the other hand, TNF seems to be a more important cytokine in the AS mechanism than in RA. Better drug survival and lower rate of lack of efficacy and adverse event in AS and spondyloarthritis have been reported by other registry studies [22,23]. Several studies have evaluated causes of therapy discontinuation in RA, and the majority demonstrated a higher rate of inefficacy [7,24].…”
Section: Discussionmentioning
confidence: 86%
“…According to Brazilian guidelines, biological agents are the second line of treatment. Therefore, we have included AS patients whose anti-inflammatory 22 Universidade Estadual do Rio de Janeiro, Reumatologia, Rio de Janeiro, RJ, Brazil 23 Hospital de Base do Distrito Federal, Brasília, DF, Brazil 24 Department of Internal Medicine, Universidade Federal do Rio Grande do Sul, Porto Alegre, RS, Brazil 25 Division of Rheumatology, Hospital de Clínicas de Porto Alegre, Porto Alegre, RS, Brazil treatment failed and RA patients whose DMARD combination (at least two) failed [16,17].…”
Section: Methodsmentioning
confidence: 99%